Präventive Tendenzen in Staat und Gesellschaft zwischen Sicherheit und Freiheit Ein deutsch-japanisches Symposium Ehrenpromotion von Keiichi Yamanaka - Yamanaka, Keiichi; Schorkopf, Frank; Jehle, Jörg-Martin (Universitätsverlag Göttingen, 2014)
How can the tension between security and personal freedom be solved in the risk society of today? This publication discusses exemplary problems and develops solutions at the level of constitutional law, public international law, economic law, criminal law, and medical law.